On Development of Entrepreneurship in Uzbekistan: Based on Sociological Data - Seitov, Azamat (International Journal of Psychosocial Rehabilitation, 2020)
Creating favorable conditions for business development is one of the main goals of economic development in Uzbekistan. Since 2018, UzLiDeP has been conducting sociological monitoring of the business climate of Uzbekistan. The article provides an analysis of generalized sociological data. Entrepreneurs in the country generally approve of government reforms in the economic sphere. First of all, they feel support from the central authorities in implementing reforms throughout the country as part of the ongoing strategy. A number of indicators are given in the materials, indicating the presence of problems on the ground with the development of entrepreneurship. The main recommendations for their elimination are given.